Investigating effective factors in the development model of faculty members at Babol university of medical sciences - Zeinab Gholamnia-Shirvani; Soleiman Ahmady; Amin Habibi (Zanjan University of Medical Sciences and Health Services, 2024)
Background & Objective: The development of faculty members contributes greatly to maintaining the quality of services and products of Medical Universities and improving the health of society. Therefore, the design of development programs should be based on a comprehensive model to attract the participation of faculty members. The present study aimed to determine the effective factors on the development model of faculty members. Materials & Methods: This analytical cross-sectional study was carried out using the census method on 363 faculty members of Babol University of Medical Sciences in 2021. The data were collected by a valid and reliable online questionnaire based on the Development Model. Statistical analysis was performed in SPSS (version 21) and AMOS (version 26) software packages. Results: Faculty members with a mean age of 47.42±7.13 participated in this study, 221 of whom (60.9%) were clinical. The total mean of the development questionnaire was 343.20±45.86 (out of 396), falling in the "good" category. The Development Model had a good fit. All path coefficients between model constructs were significant (P<0.01). The causal, intervening, and contextual conditions, central phenomenon, and development strategies were the predictors of development consequnces. The development model predicted 97%, 97%, and 100% of the variance of central phenomenon, strategies, and development consequnces, respectively. Conclusion: In this study, causal, intervening, and contextual conditions, core phenomenon, and strategies were reported as effective factors in the development of faculty members of Babol University of Medical Sciences. It is necessary to consider these factors and the structural relationships between them in the design, implementation, and evaluation of related programs according to the Development Model of faculty members.